(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Although rupture of the extensor digitorum longus or extensor pollicis longus is common after plating for the distal radius fractures, complication of flexor tendon rupture is very rare. Most of the current reports on flexor pollicis longus rupture after volar plating for distal radius fractures are related to the distal placement of the plate, second displacement, increasing the collision between the distal edge of the plate, screws and the flexor tendons will lead to tendon rupture. Objective: To warn about the delayed rupture of flexor pollicis longus rupture after volar plating for the distal radius fracture, and to discuss the factors contributing to this complication, thereby recommending figure out how to prevent the complication. Case report: Report 2 cases of delayed rupture of flexor pollicis longus after 6 months and 12 months respectively of volar butress plating and 3.5 mm screws for distal radius fractures. Results: The factors that caused flexor pollicis longus rupture in the two cases were related to the tendon impinging on the distal edge of the plate, and screws because the plate was placed distally and screws head protruded, and correction did not completely restore the bony anatomy. After 3 months of hardwere removal end to end sutures or tendon graftin, full movement of the thumb was restored. Conclusion: When opening and internal fixation, it is necessary to completely restore the bony anatomy and place the plate proximal when possible. When there are symtoms such as tendon irritation, the surgeon shoud consider removing the implant as soon as possible after the bone union is achieved to avoid the complication of tendon rupture that make the treatment much more difficult.